Integration of Psychometric Testing in Employee Recruitment and Selection to Enhance Job Fit - Suwarno, Suwarno (Universitas Dehasen Bengkulu, 2025)
This study examines the integration of psychometric testing in the recruitment and selection process to enhance employee job fit within a village administrative office. The research aims to analyze the extent to which three primary psychometric dimensions cognitive ability, personality traits, and work motivation predict job suitability among job applicants. Using a quantitative approach, data were collected through structured questionnaires and analyzed using multiple linear regression. The results show that all psychometric components significantly influence job fit, with personality traits emerging as the most dominant predictor. The validity and reliability tests confirm that all measurement instruments used are accurate and dependable. Furthermore, the classical assumption tests indicate that the regression model meets all necessary statistical criteria, ensuring the robustness of the findings. The coefficient of determination (R² = 0.659) reveals that psychometric variables explain 65.9% of the variance in job fit, while the remaining portion is influenced by other factors such as technical skills, work experience, and organizational culture. The study concludes that integrating psychometric assessments into recruitment and selection procedures enhances the objectivity and effectiveness of hiring decisions. Therefore, organizations particularly public sector offices are encouraged to adopt standardized psychometric tools as a core component of their staffing strategies.